N-ALKENYLIMIDAZOLE METAL COMPLEX DERIVATIVES AS EFFECTIVE AGENTS FOR THE HYPOXIC CONDITIONS - Svetlana Shakhmardanova; Pavel Galenko-Yaroshevsky (Belgorod National Research University, 2017)
The relevance. The therapy of hypoxemic conditions by the substances, which are differing because of their key role in the vital processes of metabolism and also their high pharmacological activity, and which are known to be the regulators of redox systems, can be considered as one of the priority directions of the modern clinical and experimental pharmacology. Metal complexes of essential elements, which are the natural participants of the ligand formation, can be very interesting in this sense. The research goal. Experimental validation of the pharmacological correction of the hypoxic conditions of the N-alkenyl-, N-propargylimidazoles and 3 hydroxypyridine metal complex derivatives. Test compounds and drugs. In comparison with well-known antihypoxants, antioxidants and actoprotectors in animal studies investigated acute toxicity, cytotoxicity, antihypoxic and actoprotective activity, effect on Central nervous system, liver, kidneys, heart, system of blood microcirculation, biochemical and hematological parameters, redox potential, studied the main ways of mechanism of action and the possibility of combined use with drugs of different pharmacological groups of complexes of zinc, cobalt, iron, derivatives of N-alkenyl-, N propargylimidazol and 3-hydroxypiridine. The discussion of the results. The researched drugs are moderately and low toxic, so it proves their safety. The antyhypoxic and actoprotective effect has been shown by the complexes of cobalt (CoALL) and iron (tetravim) and also by the derivatives of N-alkenylimidazole. Hemostimulating effect of CoAll has also been discovered. A possible mechanism of the antihypoxic effect of the test compounds could be attributed to the effect on coupling of oxidation and phosphorylation, maintenance of the mitochondria structure and functions in conditions of oxygen deficiency, elimination of the negative effect of hypoxia on carbohydrate metabolism, improvement of microcirculation and tissue oxygenation parameters and restore of the redox potential at hypoxia exposure. CoALL, probably, activates the key metabolism stages, which are responsible for energy supply by oxidizing organic substrates. The increasing of hematocrit, erythrocyte and hemoglobin levels can also be a protective factor of CoALL in condition of hypoxia. Conclusions. CoALL is promising for the further development as a hemostimulating drug, and CoALL and tetravim as antihypoxic and actoprotective drugs. Redox-regulating activity of metal complexes of the derivatives of N alkenylimidazole offers the opportunities to construct new effective preparations of a wide spectrum of action on their basis.